Empezando por el principio: análisis económico de la función del Derecho Societario - Forno Odría, Hugo (2017)
Fundamental rights as private autonomy and business freedom prevent individuals from being unjustifiably restricted from doing a risk analysis and regulating their interests as they please. A restriction is only justified when transaction costs are prohibitive, which depends of the agents that intervene on the economic sector where each regulation is directed. In this article, the author seeks to determine the necessity -if any- of Corporate Law in Peru. In order to achieve this, concepts like Coase’s theorem, the principle of regulatory subsidiarity and different company’s theories will be used and developed. Also, this article seeks to present which tools does individuals possess when a corporate regulation already in force contravenes its own function.